Pengaruh Kepemimpinan Terhadap Disiplin Kerja Karyawan Di Daima Hotel Padang - Fathiyya Zaidir; Hijriyantomi Suyuthie; Era Gumala Astia (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2026)
This study was conducted to evaluate the extent to which leadership (X) influences employees' work discipline (Y) at Daima Hotel Padang. The research employed a descriptive quantitative approach based on a causal associative research design. Data were collected through a survey using a structured questionnaire with a Likert scale. Considering the size of the population, a census (total sampling) technique was applied, involving all 53 employees as respondents. The descriptive analysis indicated that the leadership variable (X) was categorized as good, with a mean score of 4.13. Meanwhile, the work discipline variable (Y) obtained a mean score of 4.20, reflecting a good to very good category. Prior to hypothesis testing, classical assumption tests, including normality and linearity tests, were conducted to ensure the appropriateness of the data for regression analysis. The data were subsequently analyzed using simple linear regression with SPSS version 26. The hypothesis testing results revealed that leadership has a positive and statistically significant effect on employees' work discipline. This finding is supported by the regression equation Y = 33.556 + 0.409X, a calculated t-value of 4.270, which exceeds the t-table value of 2.006, and a significance value of 0.000 (< 0.05). Furthermore, the coefficient of determination (R² = 0.263) indicates that leadership accounts for 26.3% of the variance in employees' work discipline, while the remaining 73.7% is explained by other variables beyond the scope of this study. In conclusion, the findings demonstrate that stronger leadership exhibited by the Head of Department (HOD) is associated with higher levels of employee work discipline at Daima Hotel Padang.